2021
DOI: 10.3389/fphar.2020.573645
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Daprodustat for Anemia Therapy in Chronic Kidney Disease Patients: A Systematic Review and Meta-Analysis

Abstract: Objective: Daprodustat is a novel oral agent in treating anemia of chronic kidney disease (CKD), and several clinical trials have been conducted to compare daprodustat with recombinant human erythropoietin (rhEPO) or placebo. Our systematic review aimed to investigate the efficacy and safety of daprodustat for anemia treatment in both dialysis-dependent (DD) and non-dialysis-dependent (NDD) patients.Methods: Six databases were searched for randomized controlled trials (RCTs) reporting daprodustat vs. rhEPO or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…There was no trend of increasing plasma vascular endothelial growth factor (VEGF) among daprodustat-treated subjects. 64 Despite its relatively short half-life (Table 1), a 29-day phase 2 study of daprodustat in 103 HD patients demonstrated efficacy of daprodustat when administered three-times weekly at approximately twice the daily dose. 65 In a phase 3 study in Japan, 271 HD patients were randomized to continue darbepoetin or conversion to daprodustat with 52-week follow-up.…”
Section: Daprodustatmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no trend of increasing plasma vascular endothelial growth factor (VEGF) among daprodustat-treated subjects. 64 Despite its relatively short half-life (Table 1), a 29-day phase 2 study of daprodustat in 103 HD patients demonstrated efficacy of daprodustat when administered three-times weekly at approximately twice the daily dose. 65 In a phase 3 study in Japan, 271 HD patients were randomized to continue darbepoetin or conversion to daprodustat with 52-week follow-up.…”
Section: Daprodustatmentioning
confidence: 99%
“…82 Phase 3 clinical trials of sufficient duration and statistical robustness to assess MACE and other cardiovascular end-points may not be adequate to address some of these other potential complications of HIF stabilizer therapy which may be less frequent and take longer to manifest. With regards to angiogenesis, studies of vadadustat and daprodustat examined VEGF levels and reported no consistent increases; 34,64 data from phase 3 trials do not show acceleration of diabetic retinopathy; 66,83 and studies to date have not demonstrated any increase in malignancies. 84 Thrombotic events were increased in DD-CKD patients treated with roxadustat vs. epoetin 52 but similar findings have not been reported in other phase 3 studies of HIF stabilizers.…”
Section: Risks Of Hif Stabilizersmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have investigated the efficacy and safety of daprodustat in recent years. Although pervious meta-analyses ( Xie et al, 2018 ; Zheng et al, 2020a ) have shown that daprodustat could improve hemoglobin and is well tolerated in CKD patients, the evidence for its efficacy and safety in NDD patients and DD patients is still lacking. Therefore, we performed this meta-analysis and trial sequential analysis (TSA) to further evaluate the efficacy and safety of daprodustat for the treatment of CKD-associated anemia in both NDD and DD patients.…”
Section: Introductionmentioning
confidence: 99%
“…A previous meta-analysis by Zheng et al pooled data comparing the effect of daprodustat and control in anemia in patients and found that daprodustat could maintain hemoglobin with lower adverse events than rhEPO. However, they neither separated data on dialysis and non-dialysis patients nor accounted for different doses of daprodustat [ 22 ]. In addition, the previous meta-analysis compared the direct estimates of effect for only two arms at a time, in contrast to network meta-analyses that compare the efficacy of study arms directly and indirectly with no previous network meta-analysis (NMA) synthesized evidence about the safety and efficacy of all available daprodustat doses for anemia of CKDs in non-dialysis patients.…”
Section: Introductionmentioning
confidence: 99%